2011
DOI: 10.1097/fjc.0b013e318218ef21
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Blockade Does Not Enhance Apoptotic Cell Death During Ischemia and Reperfusion in Humans In Vivo

Abstract: Despite the theoretical benefits, angiotensin II type 1 receptor antagonists seem to enhance rather than reduce morbidity and mortality after myocardial infarction compared with angiotensin-converting enzyme inhibitors. This may result from unopposed angiotensin II type 2 receptor stimulation, which is associated with enhanced apoptotic cell death and increased infarct size. We studied whether the clinical effectiveness of irbesartan is hampered by enhanced apoptotic activity, detected by exposition of phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This may result from unopposed AT2 receptor stimulation, which is associated with enhanced cell apoptosis. By apoptosis imaging with 99m Tc-annexin A5, Meijer et al demonstrated that irbesartan does not induce apoptosis in transient ischemia-reperfusion in humans [22]. A recent animal study indicated that irbesartan can ameliorate the myocardial ischemia/reperfusion injury via down-regulation of apoptosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may result from unopposed AT2 receptor stimulation, which is associated with enhanced cell apoptosis. By apoptosis imaging with 99m Tc-annexin A5, Meijer et al demonstrated that irbesartan does not induce apoptosis in transient ischemia-reperfusion in humans [22]. A recent animal study indicated that irbesartan can ameliorate the myocardial ischemia/reperfusion injury via down-regulation of apoptosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of diabetes is believed to impair adequate tissue response to ischemia and further promote apoptotic cell death. 10,11 Our results showed that intravenously administered AnxV-SAv-PEcy5.5 accumulated in greater amounts in ischemic limbs of diabetic compared to nondiabetic mice. This was associated with an increased promotion of apoptosis in ischemic limbs by diabetes, as shown by greater TUNEL staining and caspase-3 activation.…”
Section: Discussionmentioning
confidence: 62%
“…However, in 2014, Advanced Accelerator Applications began producing GMP 99mTc-rhAnnexin V-128 kits which have since been in clinical trials (NCT02182609, NCT02677714, NCT02667457, NCT03232580, NCT02978885). (Hofstra et al, 2000) (Narula et al, 2001) (Belhocine et al, 2002) (Boersma et al, 2003) (Kemerink et al, 2003) ( Van de Wiele et al, 2003) (Lahorte et al, 2003) (Thimister et al, 2003) (Kartachova et al, 2004) (Kietselaer et al, 2004) (Vermeersch et al, 2004c) (Vermeersch et al, 2004a) (Vermeersch et al, 2004b) (Haas et al, 2004) (Rongen et al, 2005) (Lampl et al, 2006) (Lorberboym et al, 2006) (Kartachova et al, 2006) (Kartachova et al, 2007) (Kietselaer et al, 2007) (Van Den Brande et al, 2007) (Kartachova et al, 2008) (Kurihara et al, 2008) (Hoebers et al, 2008) (Meijer et al, 2009) (Meijer P. et al, 2011) (Meijer et al, 2009) (Engbersen et al, 2012) (Massalha et al, 2018) (Massalha et al, 2018)…”
Section: Principles Of Usementioning
confidence: 99%